Commentary: Exploring training needs of nursing staff in rural Cretan primary care settings - Maykut, Colleen (My University, 2009)
Nursing practice must be innovative and competent to meet the rapidly changing global health care system. The essential component to address these changes should be the assessment of staff education needs followed by the implementation of a focused education program. Implementation of a framework to identify specific learner's needs within their role may assist with meeting educational and workplace competencies, prudently manage health care resources, and advance quality of nursing care.
Keywords: nursing; education